Evaluasi Tingkat Kepuasan Pasien terhadap Pelayanan Swamedikasi di Apotek ABC Barokah Bawen - Anggi Dwi Saputri (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
Self-medication services are an integral part of pharmaceutical services that aim to help patients cope with minor complaints independently. Patient satisfaction is an important indicator in assessing the quality of the service. This study aims to evaluate the level of patient satisfaction with self-medication services at ABC Barokah Pharmacy, Bawen District, which has a high volume of patients but low satisfaction reviews on Google Maps. This study uses an observational descriptive design with a cross sectional approach. Primary data were collected through a structured questionnaire that was tested for validity and reliability using Cronbach's Alpha method. The questionnaire included sociodemographic characteristics as well as ten statements based on five dimensions of satisfaction: reliability, assurance, physical evidence, empathy, and responsiveness, on the Likert scale. A total of 250 respondents were obtained through the accidental sampling method according to the inclusion and exclusion criteria. Data analysis was carried out quantitatively and qualitatively. The results showed that the patient satisfaction level was in the very satisfied category with an average score of 79%. The assurance dimension obtained the highest score (88%), while empathy was the lowest (63%). The low empathy score is caused by the unavailability of communication SOPs and the high workload of pharmaceutical vocational personnel. Although self-medication services are considered good, improving the aspect of interpersonal communication between pharmacists and patients is needed to improve the quality of service as a whole.